Oral administration of Limosilactobacillus reuteri VHProbi® M07 alleviates ovalbumin-induced allergic asthma in mice. - Guoqing Meng; Hongchang Cui; Congrui Feng; Chaoqun Guo; Lei Song; Zhi Duan (PLoS ONE)
Aims Asthma is characterized by chronic airway inflammation, persistent cough, wheezing, and dyspnea. This study aimed to evaluate the efficacy of Limosilactobacillus reuteri VHProbi® M07 (M07) administration in alleviate the asthma severity in a mice model. Methods and results In vitro studies confirmed that M07 can survive and proliferate within the gastrointestinal tract. BALB/c mice were administered M07 both before and after ovalbumin (OVA) challenge. Serum levels of OVA-specific immunoglobulin (Ig) E and IgG1, inflammatory cells and cytokines in bronchoalveolar lavage fluid were assessed, along with histopathological examination of lung tissue. Compared to the placebo (PLA) group, mice treated with M07 exhibited significantly lower levels of OVA-specific IgE and IgG1 (P < 0.01). The counts of eosinophils and neutrophils were also significantly reduced in both the pretreated (PRE) group and post-treated (POS) group compared with the PLA group (P < 0.01). Histological analysis of lung tissues verified the protective effects of M07 against inflammation, demonstrating reduced infiltration of inflammatory cells. Additionally, mice in the PRE and POS groups showed significantly increased levels of IL-10 (P < 0.01), and significantly decreased levels of IL-5, IL-13, MCP-1, eotaxin, and tumor necrosis factor-α (P < 0.01). Conclusions Oral administration of M07 mitigated key features of inflammatory responses in the OVA-induced mice asthma model. These findings suggest that M07 holds therapeutic potential for the treatment of allergic asthma.